Discovery of a novel 2, 4-dimethylquinoline-6-carboxamide M4 positive allosteric modulator (PAM) chemotype via scaffold hopping. Issue 22 (15th November 2017) - Long, Madeline F.; Engers, Julie L.; Chang, Sichen; Zhan, Xiaoyan; Weiner, Rebecca L.; Luscombe, Vincent B.; Rodriguez, Alice L.; Cho, Hyekyung P.; Niswender, Colleen M.; Bridges, Thomas M.; Conn, P. Jeffrey; Engers, Darren W.; et al.
Graphical abstract: Abstract: This Letter details our efforts to replace the 3-amino moiety, an essential pharmacophore for M4 PAM activity in most M4 PAMs to date, within the thieno[2, 3- b ]pyridine core, as the β-amino carboxamide motif has been shown to engender poor solubility, varying degrees of P-gp efflux and represents a structural alert. A scaffold hopping exercise identified a novel 2, 4-dimethylquinoline carboxamide core that provided M4 PAM activity and good CNS penetration without an amino moiety. In addition, MacMillan photoredox catalysis chemistry was essential for construction of the 2, 4-dimethylquinoline core.